The authority of the Bogor Dalam Police Traffic Unit Order Arrangement And Restrictions So Cross Ciawi-Puncak National Road Based on Regulations Minister of Transportation of the Republic of Indonesia Number Pm 84 Year 2021 - Ariyanti Nur Rizki; Hana Iybah Safitri; Elis Sutiasni; Isep H. Insan; Eka Ardianto Iskandar (Novateur Publications, 2022)
Road traffic and transportation is a single system consisting of: on Then cross, transport road, network Then cross And transport road, road traffic and transportation infrastructure, vehicles, drivers, users roads and management. According to Mahipal Marhun in general traffic interpreted as the movement of human movement from one place to anotherwith tools or without tools. Traffic jams are a common problem This often happens in tourism areas and cities, according to Alokapala The main cause of congestion is the increasing tendency of users service transportation for use vehicle personal compared to vehicle general. Police Country Republic Indonesia is Wrong Oneinstitution country or government Which organize service in a manner direct to public, Wrong only one service in the field Then cross as in Law Number 22 of 2009 concerning Then Cross and Highway Article 7 Paragraph 2 Letter E. Authority according to Mirriam Budiarjo is power Which body law, prowess in carrying out legal actions, which action is carried out with the intention of causing legal consequences, and includes things that disappear and certain legal consequences. Unit Then Bogor police station own authority to act through an odd-even system, management and manipulation Then cross Which Where in accordance with Chapter 3 And Chapter 8 Regulation Minister Number 84 of 2021 concerning traffic regulation on roads nationalCiawi–PeakNumber074Andsegment road nationalPeak –limitCityCianjur Number 075 which has been established to overcome the problem of congestion in the area of the Ciawi – Puncak national road. Bogor Police Traffic Unit synergize with service liaison Regency Bogor If currently operate task in field
Keywords: Cross; Transport Road; Congestion; Unit SoCross; Department Transportation